Pengendalian Infeksi Akar Gada pada Pembibitan Kubis dengan Pupuk Hijau Daun Paitan - Pratiwi, Diah Ayu; Gutomo, Hardjono Sri; Hadiwiyono, Hadiwiyono (Universitas Sebelas Maret, 2015)
Clubroot is a major disease that often infects cabbage caused by Plasmodiophora brassicae Wor.. The leaf of T. diversifolia is an example of weeds that can be used as green leaf manure. The research aimed to study the effectiveness and dosage of green manure from Tithonia leaf to control clubroot. In planta test was conducted by using factorial completely randomized design, the first factor was dosages of Tithonia green manure and second factor was application time of fertilizing. The research showed that green manure from Tithonia leaf effectively suppressed infection of P. brassicae and was capable of increasing growth variable of cabbage seedling. Fertilizing with green leaf manure of Tithonia with dosage of 10 ton ha-1 could decreased intensity of P. brassicae infection up to 10,18%. The application time of fertilizing 0 days after planting has the highest weight of cabbage seedling biomass is 14,10 g.